Tobacco smoking and alcohol drinking at diagnosis of head and neck cancer and all‐cause mortality: Results from head and neck 5000, a prospective observational cohort of people with head and neck cancer. Issue 5 (23rd April 2018) - Beynon, Rhona A.; Lang, Samantha; Schimansky, Sarah; Penfold, Christopher M.; Waylen, Andrea; Thomas, Steven J.; Pawlita, Michael; Waterboer, Tim; Martin, Richard M.; May, Margaret; Ness, Andy R.
Abstract : Tobacco smoking and alcohol consumption are well‐established risk factors for head and neck cancer. The prognostic role of smoking and alcohol intake at diagnosis have been less well studied. We analysed 1, 393 people prospectively enrolled into the Head and Neck 5000 study (oral cavity cancer, n =403; oropharyngeal cancer, n =660; laryngeal cancer, n =330) and followed up for a median of 3.5 years. The primary outcome was all‐cause mortality. We used Cox proportional hazard models to derive minimally adjusted (age and gender) and fully adjusted (age, gender, ethnicity, stage, comorbidity, body mass index, HPV status, treatment, education, deprivation index, income, marital status, and either smoking or alcohol use) mortality hazard ratios (HR) for the effects of smoking status and alcohol intake at diagnosis. Models were stratified by cancer site, stage and HPV status. The fully‐adjusted HR for current versus never‐smokers was 1.7 overall (95% confidence interval [CI] 1.1, 2.6). In stratified analyses, associations of smoking with mortality were observed for oropharyngeal and laryngeal cancers (fully adjusted HRs for current smokers: 1.8 (95% CI=0.9, 3.40 and 2.3 (95% CI=0.8, 6.4)). We found no evidence that people who drank hazardous to harmful amounts of alcohol at diagnosis had a higher mortality risk compared to non‐drinkers (HR=1.2 (95% CI=0.9, 1.6)). There was no strong evidence that HPV status or tumour stage modified the association of smoking with survival. Smoking status at the time of a head and neck cancer diagnosis influenced all‐cause mortality in models adjusted for important prognostic factors. Abstract : What's new? Smoking and alcohol use are risk factors for developing head‐and‐neck cancer (HNC) and are known to influence mortality in general. However, the prognostic role of smoking status and alcohol intake at time of diagnosis on HNC survival is less clear. In this study, the authors provide a comprehensive, prospective analysis of mortality risk in different tumour sites, adjusting for important prognostic factors such as stage, comorbidity, and HPV infection. These results may provide insight to inform and improve prediction of clinical outcomes.